RISING CASES OF ANTIBIOTICS SELF-MEDICATION AND ITS ASSOCIATED PREDICAMENT - Attah, Friday; Angulu, Caleb Ndako; Mamman, Godiya; Udensi, Esther; Anyebe, Emmanuel Ogbole; Daniel, Elijah Ngbede; Ajanya, Benjamin Unekwuojo; Olaruwaju, Gabriel Adewale (FUDMA Journal of Sciences, 2020)
Antibiotics are medical products designed to cure or avoid bacterial infections that should be administered to patients based on a licensed health care professional’s directive. Self-medication is defined as the usage of medication, whether orthodox or traditional, for self-cure. The practice of antibiotics self-treatment is a global phenomenal. Indulgence of antibiotics self-medication had crippled the lives of many people with increase antibiotics resistance bacterial and disruption of gut microbiota. The practice of antibiotics self-medication was sustained and reinforced by easy information access on antibiotics uses and the accessibility of antibiotics in the environments. The menace of this practice is abruptly stoppage of the treatment when symptoms disappeared because of inadequate idea of the ailment. The best way to discourage antibiotics self-medication is to take the campaign to all stakeholders in antibiotics dealings to reduce the inflow of antibiotics and as well as to educate patient on the inherent dangers.